The role of laboratory biomarkers in diagnostics and management of COVID-19 patients - Perović Blagojević, Iva; Bojanin, Dragana; Ristovski-Kornic, Danijela; Marković, Jelena; Aleksić, Predrag; Subošić, Branko; Vekić, Jelena; Kotur-Stevuljević, Jelena (Archives of Pharmacy, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of a highly transmittable and heterogenic infection of the respiratory tract, characterized by a broad spectrum of clinical manifestations with a different degree of severity. Medical laboratories play an important role in early diagnosis and management of Coronavirus Disease 2019 (COVID-19) patients. Indeed, the results of several laboratory tests are essential for assessing the severity of the disease, selecting appropriate therapeutic procedures and monitoring treatment response. Routine laboratory testing in COVID-19 patients includes biomarkers of acute phase reaction, hematological and biochemical parameters that indicate tissue injury. The aim of this review paper is to describe the role of these biomarkers in the diagnostics and management of adult and pediatric COVID-19 patients.